CRISPR-Cas9-mediated knockout of CYP79D1 and CYP79D2 in cassava attenuates toxic cyanogen production - Gomez, Michael A.; Berkoff, Kodiak C.; Gill, Baljeet K.; Iavarone, Anthony T.; Lieberman, Samantha E.; Ma, Jessica M.; Schultink, Alex; Karavolias, Nicholas G.; Wyman, Stacia K.; Chauhan, Raj Deepika; Taylor, Nigel J.; Staskawicz, Brian J.; et al. (Frontiers in Plant Science, 2023)
Cassava (Manihot esculenta) is a starchy root crop that supports over a billion people in tropical and subtropical regions of the world. This staple, however, produces the neurotoxin cyanide and requires processing for safe consumption. Excessive consumption of insufficiently processed cassava, in combination with protein-poor diets, can have neurodegenerative impacts. This problem is further exacerbated by drought conditions which increase this toxin in the plant. To reduce cyanide levels in cassava, we used CRISPR-mediated mutagenesis to disrupt the cytochrome P450 genes CYP79D1 and CYP79D2 whose protein products catalyze the first step in cyanogenic glucoside biosynthesis. Knockout of both genes eliminated cyanide in leaves and storage roots of cassava accession 60444; the West African, farmer-preferred cultivar TME 419; and the improved variety TMS 91/02324. Although knockout of CYP79D2 alone resulted in significant reduction of cyanide, mutagenesis of CYP79D1 did not, indicating these paralogs have diverged in their function. The congruence of results across accessions indicates that our approach could readily be extended to other preferred or improved cultivars. This work demonstrates cassava genome editing for enhanced food safety and reduced processing burden, against the backdrop of a changing climate.